Graphic illustration of impairment: science fiction, Transmetropolitan and the social model of disability. Issue 1 (18th September 2018) - Gibson, Richard
Abstract : The following paper examines the cyberpunk transhumanist graphic novel Transmetropolitan through the theoretical lens of disability studies to demonstrate how science fiction, and in particular this series, illustrate and can influence how we think about disability, impairment and difference. While Transmetropolitan is most often read as a scathing political and social satire about abuse of power and the danger of political apathy, the comic series also provides readers with representations of impairment and the source of disability as understood by the Social Model of Disability (SMD). Focusing on the setting and fictional world in which Transmetropolitan takes place, as well as key events and illustration styling, this paper demonstrates that the narrative in this work encompasses many of the same theoretical underpinnings and criticisms of society's ignorance of the cause of disability as the SMD does. This paper aims, by demonstrating how Transmetropolitan can be read as an allegory for the disabling potential of society as experienced by individuals with impairments, to prompt readers into thinking more creatively about how narratives, seemingly unconcerned with disability, are informed and can be understood via disability theory.